2006
DOI: 10.1258/000456306778904597
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the albumin cobalt binding (ACB®) assay for measurement of ischaemia-modified albumin (IMA®) on the Beckman Coulter LX-20

Abstract: Background In the presence of ischaemia, albumin undergoes changes resulting in the formation of ischaemia-modified albumin (IMA). Increased serum concentrations of IMA have been found in patients with myocardial ischaemia. The purpose of this study was threefold: to evaluate the albumin cobalt binding (ACB) assay for measurement of IMA on the Beckman Coulter LX-20; to establish a reference range for IMA; and to investigate the relationship between IMA and total albumin concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…Отсутствие корреляции между измеренным уровнем альбумина и КСС находится в известном противоречии как собственно с предложенной моделью [6], так и с результатами других авторов [9]. Однако, и эти результаты далеко неоднозначны.…”
Section: результаты и обсуждениеunclassified
See 1 more Smart Citation
“…Отсутствие корреляции между измеренным уровнем альбумина и КСС находится в известном противоречии как собственно с предложенной моделью [6], так и с результатами других авторов [9]. Однако, и эти результаты далеко неоднозначны.…”
Section: результаты и обсуждениеunclassified
“…Анализ взаимозависимости показателей пациентов с аутоиммунными заболеваниями показал, что для данной группы пациентов характерно появление значимой (р<0,05) корреляции между КСС и уровнем альбумина (R 2 =0,14), сопоставимый с величинами обнаруженными в других исследованиях [9]. Однако, того же порядка (R 2 =0,15) оказалась и степень связи с уровнем глобулинов (метод с п-диметиламинобензальдегидом).…”
unclassified
“…The assay can be performed manually with a spectrophotometer, however it was also initially automated on the Cobas MIRA Plus (Roche Diagnostics) automated spectrophotometer [41]. The assay has since been adapted for other automated clinical chemistry platforms including the LX-20 (Beckman Coulter, Brea, CO, USA) [42], Hitachi 911 (Hitachi, Japan) [43] Hitachi 7600 (Hitachi, Japan) [44] and the Konelab 20 (Thermo Scientific, United Kingdom) [45]. To date a commercialised point of care device for IMA remains to be developed however a precommercial portable spectrophotometer and IMA assay has been developed by (Microwells Biotechnology Co. Ltd, Shanghai, China).…”
Section: Non Ischemicmentioning
confidence: 99%
“…There is a relationship between IMA values and serum albumin levels, although this is much less marked across the reference interval for albumin 37. The use of an albumin-adjusted correction has been proposed,38 although a reference interval study found albumin correction to have little impact compared with other analytical factors 39. However, it has been reported that the changes in IMA observed in patients with chest pain were attributable only to changes in the albumin concentration 40.…”
Section: Laboratory Aspectsmentioning
confidence: 99%
“…However, it has been reported that the changes in IMA observed in patients with chest pain were attributable only to changes in the albumin concentration 40. The method was originally developed for use on the Cobas Mira, where it shows good analytical performance41 but it has also been implemented on Roche and Beckmann platforms 30 39. When implemented on different platforms, there are changes in the reference interval and decision threshold 39…”
Section: Laboratory Aspectsmentioning
confidence: 99%